Band alignment and charge transport study of Au nanoparticles decorated over MoS2/MoSe2 hybrid heterostructure for plasmon enhanced photodetection. (15th March 2023) - Mathew, Sanjana; Chandu, K.K. Sai; Halder, Sayan; Polumati, Gowtham; Chakraborty, Chanchal; Sahatiya, Parikshit; Pal, Subhradeep
Abstract: This paper demonstrates the fabrication of MoS2 /MoSe2 hybrid heterostructure and decorating it with Au nanoparticles for enhanced photodetection. The measured responsivity values of the fabricated devices at 505 nm with and without Au nanoparticles were found to be 2.54 A/W and 0.262 A/W suggesting a clear indication of the enhanced photodetection with Au NPs. Detailed band alignment studies of the hybrid heterostructure are performed using Ultra-Violet Photoelectron Spectroscopy (UPS) which also explains the real-time charge transport phenomenon of the fabricated device. Further, simulations and numerical analysis for Au decorated MoS2 /MoSe2 are performed to understand the electrical field distribution across Au NPs and the enhancement of absorption due to Mie Scattering. Successful demonstration of plasmon-enhanced photodetection of MoS2 /MoSe2 will be essential in the field of 2D plasmonics with potential applications in optical detection in the harsh environment, photovoltaic solar energy conversion, chemical sensing applications, etc.